2018
DOI: 10.1017/s1355770x18000244
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal shortage risk and the potential role for tropical storm insurance: evidence from the Caribbean

Abstract: Recently a number of multi-country insurance schemes have been introduced to deal with short-term fiscal liquidity gaps after natural disasters. However, little is known about the actual underlying risk to the fiscal sector just after such events. In this paper, we estimate the risk of fiscal shortages due to tropical storms in the Caribbean. To this end, first we use a panel VAR and estimate that while government expenditure does not respond to damages due to tropical storms, there is a significant contempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…This result can be seen in Table 6, panel 2 (affected people variable), which shows that disasters significantly increase capital expenditure at the district level in the year following a disaster. These results stray from those of Ouattara et al (2018), who found that disasters do not significantly affect capital expenditure in the Caribbean. Other resources, such as international aid, are likely a reason for the differences between our study and their study.…”
Section: Estimation Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…This result can be seen in Table 6, panel 2 (affected people variable), which shows that disasters significantly increase capital expenditure at the district level in the year following a disaster. These results stray from those of Ouattara et al (2018), who found that disasters do not significantly affect capital expenditure in the Caribbean. Other resources, such as international aid, are likely a reason for the differences between our study and their study.…”
Section: Estimation Resultscontrasting
confidence: 92%
“…All fiscal data were provided by the Directorate-General for Financial Balance at the Indonesian Ministry of Finance (MoF). In line with Ouattara et al (2018), we converted all values into natural logged form. Local own-source revenue includes local taxes, levies, and other authorized sources such as profits from the selling of local assets, goods, and services; interest income from savings; currency exchange profits; and compensation.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Mejia (2014) investigated natural disasters (hurricane and floods) and their impact on per capita GDP and the debt to GDP ratio in 12 Caribbean countries. Ouattara et al (2018) measured the impact of hurricanes on government spending in a set of Caribbean countries. 4. https://www.onecaribbean.org/ 5.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%